2022
DOI: 10.1177/14614456221136975
|View full text |Cite
|
Sign up to set email alerts
|

When a request turn is segmented: Managing the deontic authority via early compliance

Abstract: By drawing on service encounter data in Japanese, this paper analyzes a previously undocumented request action initiated by a service provider to a client as a necessary step to provide the service. The service provider and their client, both exercising respective deontic rights, collaboratively construct a request turn in particular ways. In this case, due to the Japanese SOV word order, the service provider takes advantage of segmenting their request turn to allow the recipient clients to begin compliance, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…As evidenced above (see section 2.2.1), it is still debated whether visuospatial behaviour can be organized in adjacency pairs, and thus whether it can reveal orientations to deontic stances and statuses. However, some research has revealed visuospatial managements of deontic rights (see for instance Asmuß & Oshima, 2012;Barske, 2009;Clifton et al, 2018;Kuroshima, 2023;Stevanovic & Monzoni, 2016;Tranekjaer et al, 2022;Tuncer, 2015;Van De Mieroop et al, 2020). This thesis adds to that research by investigating how participants negotiate rights to propose and depict through visuospatial resources.…”
Section: Deonticsmentioning
confidence: 91%
See 4 more Smart Citations
“…As evidenced above (see section 2.2.1), it is still debated whether visuospatial behaviour can be organized in adjacency pairs, and thus whether it can reveal orientations to deontic stances and statuses. However, some research has revealed visuospatial managements of deontic rights (see for instance Asmuß & Oshima, 2012;Barske, 2009;Clifton et al, 2018;Kuroshima, 2023;Stevanovic & Monzoni, 2016;Tranekjaer et al, 2022;Tuncer, 2015;Van De Mieroop et al, 2020). This thesis adds to that research by investigating how participants negotiate rights to propose and depict through visuospatial resources.…”
Section: Deonticsmentioning
confidence: 91%
“…Consequently, I hope to contribute to literature on proposals and joint decision-making (cf. -Kuhlen, 2014;Houtkoop, 1987;Lindholm et al, 2020;Lindström, 2017;Nissi, 2015;Stevanovic, 2012Stevanovic, , 2015Stevanovic, , 2021Stevanovic & Monzoni, 2016;Stivers & Sidnell, 2016;Thompson et al, 2021), particularly on how visuospatial resources become relevant, both for the formation of proposals, and for negotiations of deontic rights (Clifton et al, 2018;Kuroshima, 2023;Magnusson, 2022;Stevanovic, 2015Stevanovic, , 2018Stevanovic, , 2021Stevanovic & Peräkylä, 2012Van de Mieroop et al, 2020).…”
Section: Aimmentioning
confidence: 99%
See 3 more Smart Citations